Morphology and structure of lead‐free CuSb‐based double perovskites for photocatalytic CO2 reduction. Issue 3 (14th October 2022) - Wu, Daofu; Tian, Changqing; Zhou, Jingchen; Huang, Yanyi; Lai, Junan; Gao, Bo; He, Peng; Huang, Qiang; Tang, Xiaosheng
Abstract: Lead‐free halide double perovskites (DPs) have attracted great attention due to their stability, nontoxicity, and good photophysical properties. Herein, environmentally friendly small‐bandgap Cs2 CuSbCl6 and Cs4 CuSb2 Cl12 DPs microcrystals (MCs) are prepared via a solvent synthesis technique. This study also reports a bottom‐up synthetic protocol for obtaining evenly distributed Cs2 CuSbCl6 and Cs4 CuSb2 Cl12 quantum dots (QDs) utilizing a modified hot injection approach. These MCs and QDs have strong absorption throughout the visible region, indicating that they could be promising light‐absorbing materials as sunlight‐driven photocatalysts. For the first time, the efficient sunlight‐driven photocatalytic CO2 reduction activity of these Pb‐free "green" MCs and QDs has been revealed, and a product yield of 307 μmol g −1 and an electron consumption of 1053 μmol g −1 are achieved by the Cs4 CuSb2 Cl12 QDs under 3 h irradiation. Our results highlight the potential of this family of materials for photocatalytic applications. Abstract : Environmentally friendly small‐bandgap Cs2 CuSbCl6 and Cs4 CuSb2 Cl12 halide double perovskites microcrystals and quantum dots (QDs) are fabricated successfully, and the Cs4 CuSb2 Cl12 QDs present an impressive electron consumption of 1053 µmol g −1 under 3 h illumination.